X-Prolyl-Dipeptidyl Aminopeptidase of Lactobacillus delbrueckii subsp. bulgaricus: Characterization of the Enzyme and Isolation of Deficient Mutants - Atlan, Danièle (1990)
Lactobacillus delbrueckii subsp. bulgaricus CNRZ 397 is able to hydrolyze X-proline-para-nitroanilides and X-proline-β-naphthylamides (X for alanyl- or glycyl-). A single metal-independent cytoplasmic enzyme with a molecular weight estimated to be 82,000 is responsible for these activities and was named X-prolyl-dipeptidyl aminopeptidase (X-Pro-DPAP). Isolation and analysis of mutants totally deficient for X-Pro-DPAP activity showed that a total lack of this enzyme induces (i) a decrease in the growth rate; (ii) an increase in cell wall proteinase activity; (iii) the loss of three cell wall proteins with respective molecular masses of 16, 40, and 52 kilodaltons; and (iv) enhancement of a cell wall protein with a molecular mass of 150 kilodaltons. The involvement of X-Pro-DPAP in casein catabolism is discussed.